Prehistoric cereal foods of southeastern Europe: An archaeobotanical exploration. (April 2019) - Valamoti, Soultana Maria; Marinova, Elena; Heiss, Andreas G.; Hristova, Ivanka; Petridou, Chryssa; Popova, Tzvetana; Michou, Stavroula; Papadopoulou, Lambrini; Chrysostomou, Panagiotis; Darcque, Pascal; Grammenos, Dimitrios; Iliev, Stanislav; et al.
Abstract: This paper addresses for the first time a large body of archaeobotanical data from prehistoric Southeastern Europe, mostly published for the first time, that correspond to cereal food preparations. The evidence presented here comes from 20 sites situated in Greece and Bulgaria, spanning the Early Neolithic through to the Iron Age (7th millennium B.C.-1st millennium B.C.). The remains correspond to cereal fragments or agglomerations of fragments that resulted from ancient food preparation steps such as grinding, boiling, sprouting/malting, mixing in bread-like or porridge-like foodstuffs. The article builds on previous pilot studies and with the aid of stereomicroscopy and scanning electron microscopy offers a first classification and possible interpretations of the finds leading to the recipes that might have generated them. At the same time the article highlights the significance of retrieving and studying in depth such rare archaeobotanical finds, points out the interpretative problems stemming from such material and suggests ways forward to address similar archaeological finds in different parts of the world. The paper demonstrates the potential of the systematic study of cereal-based food remains, in our case prehistoric Southeastern Europe, to reveal a wide variability in cereal food transformation practices, suggestive of the interplay between available ingredients, cultural traditions and the complex interaction between society and environment. Highlights: Cereal food remains from Southeastern Europe spanning the 7th to the 1st millennium B.C. reveal considerable variability. A new classification system is proposed for the study of cereal-based food remains. Classification criteria are based on macroscopic and microscopic observations informed by ethnography. A wide range of potential cereal food preparations in prehistory cautions against hasty identifications.